Feasibility study on musculoskeletal disorders and safety-related issues among maintenance workers and competent chargeman in a voltage installation / Muhammad Firdaus Darduri - Muhammad Firdaus, Darduri (2018)
Electrical work associated with musculoskeletal disorders and safety issues related with voltage installation is common issues to discuss. In addition, the work of voltage installation is a work that requires repetitive motions, awkward postures, manual handling and involves with heavy equipment such as wind circuit breaker, vacuum circuit breaker and meter installation. In the utility industry, voltage installation work must be done by skilled and semi-skilled workers as it involves electrical operations that a failure to operate properly may cause injuries and accidents at workplace. The main objectives of this feasibility study were to evaluate musculoskeletal disorders during voltage installations and evaluate safety issues during voltage installations. Research methods namely Hazard Identification, Risk Assessment and Control measure (HIRAC) to assess safety issues for voltage installation work, and Nordic musculoskeletal questionnaire (NMSDQ) to assess musculoskeletal disorders in voltage installations were employed. 20 respondents from engineering department of Malakoff Utilities Sdn. Bhd. Data were analyzed to get the crucial information to identify weaknesses in aspects of safety issues and musculoskeletal disorders during voltage installation work. The data showed that safety issues for voltage installation work, work safety hazards, risk assessment and control measures were in low likelihood but the severity was high because they involved electric shock and fatality was at stake. For body posture when performing the job steps in the voltage installation work, the likelihood was low but the severity was moderate and there was no existing control measure. Finally, Recommendation in this study, for employees and employers, if taken seriously might help them reducing the risk of fatality and musculoskeletal disorders while performing voltage installation work as well as reducing medical costs. For employers, their returns on investment are in terms of work efficiency, and medical and store maintenance cost reductions.